Aerosol indirect effects on orographic clouds and precipitation - Chavez, Steven P.; Barros, Ana P. (Frontiers in Earth Science, 2023)
The sensitivity of warm cloud development and orographic precipitation processes to aerosol indirect effects were investigated through aerosol-aware WRF (Weather Research and Forecast) V4.2.2 model simulations conditional on weather regime contrasting aerosol-cloud-precipitation interactions (ACPI) using the default aerosol in WRF and aerosol measurements from IPHEx (Integrated Precipitation and Hydrology Experiment) in the Southern Appalachian Mountains (SAM) for three different rainfall events: 1) enhanced local convection; 2) a frontal system, and 3) a tropical system. Simulations show that using the IPHEx aerosol activation spectrum yields higher Cloud Drop Number Concentration (CDNC) than the default WRF aerosol activation spectrum, with smaller cloud droplets and delayed onset of rainfall under weak synoptic forcing conditions. Evaluation against aircraft measurements in isolated convective clouds reveals that while the microphysics scheme falls short of reproducing the vertical structure of non-precipitating clouds, the simulated liquid water content (LWC) and CDNC variability near the cloud base are in close agreement with observations. The simulated cloud vertical structure from CDNC shows the regional signature of orographic cloud development over the SAM in contrast with the adjacent plains. In the inner region, valley-ridge circulations organize the spatial patterns of cloudiness under weak synoptic forcing conditions. The formation of early afternoon low-level clouds over the ridges in the summertime reflects the high sensitivity of cloud mixing ratios and cloud droplet concentrations to aerosol activation properties. For large-scale systems with strong and sustained moisture convergence at low levels (frontal and tropical systems), mechanically forced rainfall efficiency is enhanced despite high CDNC, there is no delay in the onset of precipitation, and the impact of ACPI on the spatial and temporal variability of rainfall is negligible consistent with rainfall observations. This study suggests that the diurnal cycle and the spatial variability of orographic rainfall at the event scale are strongly tied to the sensitivity of ACPI to weather regimes.